Pelatihan Pendampingan Meningkatkan Keterampilan Menyusun Instrumen Penilaian Berbasis Hots Bagi Guru MIPA MTSN 1 Kampar - Yanti, Beni (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2022)
The purpose of this research is to carry out development training to improve teachers' skills in preparing HOTS-based assessment instruments for teachers of science clumps (MIPA). This type of research is School Action Research (PTS), which was conducted at Madrasah Tsanawiyah Negeri 1 Kampar on Jalan Transad No.7, Lereng Village, Kuok District, Kampar Regency, Riau Province in the even semester of the 2020/2021 academic year for three months starting from February to April 2021. Data collection methods in this study are observation, field notes and questions. The data analysis technique uses comparative descriptive. The subjects of this study were Science and Mathematics teachers with a total of 11 teachers. Consisting of 5 Mathematics teachers and 6 Science teachers. The research action was carried out with procedures based on the principles of Kemmis and Taggart in Ulfatin which included four activities, namely planning, implementation of action, observation, and reflection or evaluation (Prof. Dr. Nurul Ulfatin, 2022). The validation technique was carried out using data triangulation technique. The results of the study obtained an average value of teacher skills in pre-development training activities of 61 points which are classified as quite good, in cycle I activities there was an increase of 11% with an average value of 72 points in the predicate good. And in cycle III there was also an increase of 12% with an average score of 84 points with details of 3 teachers with very good predicates, and 8 teachers had good predicates. So overall the development training actions to improve the skills of MIPA teachers in preparing HOTS-based assessment instruments have met the criteria for achieving success indicators ≥ 80%